Odpowiedzi

  • Użytkownik Zadane
2009-09-20T20:45:46+02:00
A) (x+3)(x-7)=x²-7x+3x-21=x²-4x-21
b) -3(2x-1)(x+6)=-3(2x²+12x-x-6)=3(2x²+11x-6)=6x²+33x-18
c) -(y-1)(2y+4)=-(2y²+4y-2y-4)=-(2y²+2y-4)=-2y²-2y+4
d) 2a²-(a+6)(2a-1)=2a²-(2a²-a+12a-6)=2a²-2a²+a-12a+6=-11a+6
e) 3(x²-1)-(x-3)(x+2)=3x²-3-(x²+2x-3x-6)=3x²-3-x²-2x+3x+6=2x²+x+3
2009-09-20T20:48:03+02:00
A) (x+3)(x-7)= x² - 7x+3x-21 = x²-4x-21
b) -3(2x-1)(x+6)= (-6x+3)(x+6)= -6x-36+3x+18 = -3x-18
c) -(y-1)(2y+4)= -(2y²+4y-2y-4) = -(2y²+2y-4) = -2y²-2y+4
d) 2a²-(a+6)(2a-1)= 2a²-(2a²-a+12a-6) = 2a²-2a²+a-12a+6 = -11a+6
e) 3(x²-1)-(x-3)(x+2)= 3x²-3-(x²+2x-3x-6) = 3x²-3-x²-2x+3x+6 = 2x²+x+3
Najlepsza Odpowiedź!
2009-09-20T20:51:01+02:00
A) (x+3)(x-7)=x²-7x+3x-21=x²-4x-21
b) -3(2x-1)(x+6)=-3(2x²+12x-x-6)=-6x²-36x+3x+18=-6x²²-33x+18
c) -(y-1)(2y+4)=-(2y²+4y-2y-4)=-2y²-4y+2y+4=-2y²-2y+4
d) 2a²-(a+6)(2a-1)=2a²-(2a²-a+12a-6)=2a²-2a²-11a+6=-11a+6
e) 3(x²-1)-(x-3)(x+2)=3x²-3-(x²+2x-3x-6)=3x²-3-x²+x+6=2x²+x+3